DETERMINANT FACTORS FOR CENTRAL LINE-ASSOCIATED BLOOD STREAM INFECTIONS (CLABSI) IN NEONATES: Faktor Determinan Central Line-Associated Blood Stream Infections (CLABSI) Pada Neonatus - Nihar, Mahdiyyah Husna; Martini, Santi; Husada, Dominicus (Jurnal Berkala Epidemiologi, 2025)
Background: CLABSI accounts for 70% of all hospitalized bloodstream infections, especially in premature infants. CLABSI in neonates can compromise the immune system and future quality of life. Purpose: This study aims to identify determinant factors associated with CLABSI in neonates.  Methods: This research was a scoping review study of three international databases namely Science Direct, PubMed, and ProQuest from January 2021-April 2024. Keyword selection refers to PCC (Populations, Concepts, Categories), with the keywords used "factor" AND "associated" AND "CLABSI" AND ("neonate" OR "newborn") AND "hospital." The selection process is depicted with PRISMA-ScR. Results: A total of 14 articles met the criteria and objectives of the study. The articles obtained        represented   all continents, which were conducted in the Americas (29%), Europe (29%), Asia (29%), and Africa (13%). Risk factors for CLABSI in neonates are grouped into two, namely intrinsic and extrinsic factors. Prevention of CLABSI in neonates can be done by modifying extrinsic factors, namely with proper aseptic technique, supervision, and management strategies. Conclusion: The determinant factors of CLABSI in neonates include intrinsic factors (gestational age of <27 weeks or preterm, comorbidities, being born by cesarean section, low birth weight, being previously treated with antibiotics, and having underlying surgical conditions) and extrinsic factors (the type of catheter, the amount of catheter lumen, long duration of insertion, insertion location at the femoral and internal-jugular access site, parenteral nutrition, and large microbial colonization at the insertion site).